Investigation of the manipulation of phagocytes by Staphylococcus aureus - O'Keeffe, Kate (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2015)
The increasing prevalence of antibiotic resistance in Staphylococcus aureus (S. aureus) heralds the advent of a "post-antibiotic era" that urgently necessitates the development of novel treatment methods such as vaccines and immunomodulatory therapies to provide an alternative to antibiotics. In order to facilitate development in these therapeutic areas, a greater understanding of the interactions between this bacterium and the host is required. S. aureus' infective prowess stems from its vast capacity for immune evasion. In recent years, it has been established that this bacteria is even capable of survival within phagocytes, the archetypal killing cells of the immune system. It has been proposed that this ability of S. aureus to survive within phagocytes is likely a critical factor facilitating dissemination. This thesis proposes that S. aureus survives inside phagocytes by subversion of autophagy and manipulates apoptosis to prolong the availability of this niche.
Keywords: Biochemistry and Immunology, Ph.D.; Ph.D. Trinity College Dublin.